The Differential Effects of Virtual Reality (VR) on the Novice and Experienced VR Users - Jun, Youjung (Asia Marketing Journal (Online), 2023)
Although research on Virtual Reality (VR) has uncovered numerous technical advantages of VR over traditional media, little is known about how individual VR users with varying prior experience respond to VR differently. This paper examines the effect of users' prior VR experience on their subsequent real-life behavior in the domain of charitable consumption. Specifically, we find that compared to experienced VR users, novice VR users are more likely to support a charitable cause in real life (e.g., ocean conservation) after experiencing this cause in VR. The increased support among novice VR users occurs because they perceive the use of VR to be more novel. We find a boundary of this effect such that when VR is used to promote a noncharitable cause, novice VR users no longer increase their real-life support after VR. This research offers new possibilities for future studies on the use of VR in societal marketing.